Black pill: how I witnessed the darkest corners of the internet come to life, poison society, and capture American politics - Reeve, Elle (ATRIA Books, 2024)
"A kaleidoscopic combination of deeply sourced, on-the-ground reporting and novelistic storytelling, detailing America at a crossroads as the battle between the right and left spills out from the dark corners of the internet into the real world"--